2019
DOI: 10.1371/journal.pone.0219827
|View full text |Cite
|
Sign up to set email alerts
|

A serious game to explore human foraging in a 3D environment

Abstract: Traditional search tasks have taught us much about vision and attention. Recently, several groups have begun to use multiple-target search to explore more complex and temporally extended "foraging" behaviour. Many of these new foraging tasks, however, maintain the simplified 2D displays and response demands associated with traditional, single-target visual search. In this respect, they may fail to capture important aspects of real-world search or foraging behaviour. In the current paper, we present a serious g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
(82 reference statements)
0
22
0
Order By: Relevance
“…In two recent papers, we introduced the concept of "foraging tempo" and speculated that the rate of successive target selections helps determine patterns of run behavior in multiple target search (Prpic et al, 2019;. Specifically, our analysis of previous studies showed that the tendency to switch randomly between target categories was more common when the interval between responses was longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two recent papers, we introduced the concept of "foraging tempo" and speculated that the rate of successive target selections helps determine patterns of run behavior in multiple target search (Prpic et al, 2019;. Specifically, our analysis of previous studies showed that the tendency to switch randomly between target categories was more common when the interval between responses was longer.…”
Section: Discussionmentioning
confidence: 99%
“…Kristjánsson et al, 2014;T. Kristjánsson et al, 2018; and 3D (T. Prpic et al, 2019) cancellation tasks to explore human foraging under conditions of varying attentional load. This work was directly inspired by the animal foraging literature (Dawkins, 1971;Heinrich et al, 1977;Jackson & Li, 2004;Pietrewicz & Kamil, 1979;Tinbergen, 1960).…”
Section: Introductionmentioning
confidence: 99%
“…We suggested that adding time pressure in this way changed levels of concentration, facilitating switching. Similarly, when we explicitly controlled the tempo at which participants were allowed to respond , we found that the majority were able to switch frequently given sufficient time between selection events (see also Prpic et al, 2019;Thornton et al, 2019). These findings suggest that the use of extended runs in our original iPad tasks occurred, at least in part, because participants chose to prioritize response speed, making switching under conjunction conditions more effortful (Gray et al, 2006;Gray & Boehm-Davis, 2000;Gray & Fu, 2004).…”
Section: Discussionmentioning
confidence: 67%
“…In our previous work, we have used simple, game-like 2D (e.g., Jóhannesson et al, 2016Jóhannesson et al, , 2017Á. Kristjánsson et al, 2014;Thornton et al, 2019) and 3D (T. Kristjánsson, Draschkow, et al, 2020;Prpic et al, 2019) tasks to explore such foraging behaviour in humans. As noted above, these studies form part of a more general research trend exploring multiple-target visual search in humans (e.g., Cain et al, 2012;Fougnie et al, 2015;Gilchrist et al, 2001;Hills et al, 2012Hills et al, , 2013Pellicano et al, 2011;Wolfe, 2013;Wolfe et al, 2016Wolfe et al, , 2019.…”
Section: Attention and Human Foragingmentioning
confidence: 99%
“…Over the past years, there has been a growth in software applications that combine game-like features with health related goals such as diagnosis of cognitive impairments. Spatial cognition in particular, lends itself well to serious-gaming adaptations as illustrated by applications such as ''Sea Hero Quest'' (Coutrot et al, 2018), ''Navigeren kun je leren'' and ''Squirrel away'' (Prpic et al, 2019). While substantial progress is being made in regards to the diagnosis of spatial impairments using these tools, the validity of treatment applications has yet to be explored.…”
Section: Discussionmentioning
confidence: 99%